Convenient site-selective protein coupling from bacterial raw lysates to coenzyme A-modified tobacco mosaic virus (TMV) by Bacillus subtilis Sfp phosphopantetheinyl transferase - Geiger, Fania; Wendlandt, Tim; Berking, Tim; Spatz, Joachim P.; Wege, Christina (Virology, 2023)
A facile enzyme-mediated strategy enables site-specific covalent one-step coupling of genetically tagged luciferase molecules to coenzyme A-modified tobacco mosaic virus (TMV-CoA) both in solution and on solid supports. Bacillus subtilis surfactin phosphopantetheinyl transferase Sfp produced in E. coli mediated the conjugation of firefly luciferase N-terminally extended by eleven amino acids forming a ‘ybbR tag’ as Sfp-selective substrate, which even worked in bacterial raw lysates. The enzymes displayed on the protein coat of the TMV nanocarriers exhibited high activity. As TMV has proven a beneficial high surface-area adapter template stabilizing enzymes in different biosensing layouts in recent years, the use of TMV-CoA for fishing ybbR-tagged proteins from complex mixtures might become an advantageous concept for the versatile equipment of miniaturized devices with biologically active proteins. It comes along with new opportunities for immobilizing multiple functionalities on TMV adapter coatings, as desired, e.g., in handheld systems for point-of-care detection.